MENSTIMULASI MINAT DAN INOVASI SISWA SMK DI BIDANG TEKNOLOGI PERKERETAAPIAN MELALUI STUDI LAPANGAN - Dara Aulia Feryando; Dhina Setyo Oktaria; Agustinus Prasetyo Edy Wibowo; Santi Triwijaya; Fathurrozi Winjaya; Ainun Fikria (Universitas Muhammadiyah Mataram, 2023)
Abstrak: Sejak tahun 2021, ujian nasional sebagai syarat kelulusan bagi para siswa tingkat akhir telah ditiadakan. Sebagai gantinya, siswa wajib mengikuti ujian yang diadakan oleh satuan pendidikan. Di beberapa Sekolah Menengah Kejuruan (SMK), ujian sekolah adalah berupa proyek akhir. Siswa diminta untuk membuat alat yang bermanfaat untuk mengatasi masalah di lingkungan sekitarnya. Dalam pengabdian masyarakat ini, edukasi tentang teknologi perkeretaapian dilakukan untuk menarik menumbuhkan minat dan inovasi para siswa SMK di bidang teknologi perkeretaapian. Selain itu, kegiatan ini diharapkan dapat memacu inovasi para siswa dalam pengerjaan proyek akhir.Melalui kegiatan ini, siswa diharapkan dapat mengetahui beberapa teknologi perkeretaapian dan berinisiatif untuk membuat alat yang dapat bermanfaat di lingkungan perkeretaapian sebagai proyek akhirnya. Kegiatan edukasi dilakukan kepada 24 siswa SMK Subulul Huda dengan metode pemberian materi ceramah di kelas dan studi lapangan . Metode evaluasi untuk mengukur tingkat keberhasilan kegiatan yaitu yang digunakan dalam kegiatan ini yaitu menggunakan metode tanya-jawab dan umpan- balik. Hasil evaluasi menunjukkan bahwa persentase tingkat keberhasilan pada sesi materi di kelas adalah 80% dan pada sesi lapangan adalah 90%. Hasil tersebut mengindikasikan bahwa kegiatan pengabdian kepada masyarakat telah terselenggara dengan baik.Abstract: Since 2021, the national exam as a graduation requirement for final year students has been abolished. Instead, students are required to take exams held by the education unit. In several Vocational High Schools (SMK), the school exam is in the form of a final project. Students are asked to make useful tools to overcome problems in the surrounding environment. In this community service, education about railways is carried out to foster interest and innovation among vocational school students in the field of railway technology. Through this activity, students are expected to be able to understand several railway technologies and take the initiative to make tools that can be useful in the railway environment as their final project. Educational activities were carried out for 24 students of Subulul Huda Vocational School using lecture methods in class and field studies. The evaluation method used in this activity is the question-answer and feedback method. The evaluation results show that the success rate in class material sessions is 80% and in field sessions is 90%. These results indicate that the activities have been carried out well.Since 2021, the national exam as a graduation requirement for final year students has been abolished. Instead, students are required to take exams held by the education unit. In several Vocational High Schools (SMK), the school exam is in the form of a final project. Students are asked to create useful tools to overcome problems in the surrounding environment. In this community service, education about railway technology was carried out to attract students' interest in the railway sector. Apart from that, it was hoped that this activity could spur students' innovation in working on their final projects. Educational activities were carried out by providing material in class and field study. The two evaluation methods used in this activity were the question-and-answer method and feedback. The evaluation results showed that the percentage success rate in class material sessions was 80% and in field sessions was 90%. These results indicate that community service activities have been carried out well.